Inquiry about self-assessment practices in Peruvian higher education students: an exploratory study - Gallardo Córdova, Katherina Edith (2023)
This study examined the self-assessment learning practices of student teachers in Peru. The research design employed an exploratory approach, and the sample consisted of 201 students, predominantly women, aged between 20 and 24 years. The Learning Self-Assessment Questionnaire, previously validated in Ecuador and Mexico, was adapted and used to ensure content validity for the Peruvian context. The findings revealed that the students relied more on self-grading processes, primarily for summative purposes, rather than engaging in self-evaluations with formative intentions. Consequently, they lacked the ability to effectively utilize self-assessment information to regulate their own learning, thereby limiting the development of metacognitive processes. This finding is paradoxical considering that these student teachers will be responsible for facilitating the learning processes of future students. The study concludes with suggestions for future research aimed at strengthening the culture of self-assessment.